PERILAKU INVESTOR GALERI INVESTASI BEI DENGAN AB MITRA SINARMAS SEKURITAS JAWA BARAT - Sri Zaniarti; Ida _; Fransisca Novita (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2017)
High inflation impacts an increase of the goods price but sometimes, it doesn’t follow the increase ofincome.Investment is a way that can be used to multiply wealth. Stocks is one of the types of investment on the capital market.The development of the capital market is very rapid and the capital market is well know among students with the establishment of an Galeri Investasi at the University.This study would like to discuss about behavior of investor. This study used a survey method by distributing questionnaires to 220 respondents, who are Investors of Galeri Investasi BEI AB Mitra Sinarmas Securitas, West Java. The method used to test the correlationbetween decision factors (fundamental factor, technical analysis, age and experience) and investment decision (frequency of stocks trading and business area of the company) using correlation rank Spearman test. The results showed there is significant correlation between technical analysis and frequency of stocks trading but there are not significant correlation betweenFundametal Factor and business area of the company, age and frequency of trading stock, experience and frequency of stocks trading.Keywords: behavior of investor, decision factors, investment decision